Lived experiences and coping strategies of persons seeking infertility treatment in the Kumasi metropolis: a descriptive phenomenological study - Louisa Annan-Frey; Edward Appiah Boateng; Alberta Lomotey; Christopher Lartey; Veronica Dzomeku (BMC, 2023)
Abstract Background Women seeking fertility treatment face myriad challenges that they must adapt and adjust to daily. This aimed at exploring the experiences and coping strategies of such persons in the Kumasi. Metropolis. Methods A qualitative approach was employed and a purposive sampling technique was used to select 19 participants. A semi-structured interview was used to collect data. The data collected were analyzed using Colaizzi's method of data analysis. Results Persons living with infertility had emotional experiences of anxiety, stress, and depression. Socially, participants experienced isolation, stigma, societal pressure, and marital problems due to their inability to conceive. The key coping strategies adopted were spiritual (faith-based) and social support. Though formal child adoption can be an option, no participant preferred it as a coping strategy. Some participants also reported using herbal medicine before going to the fertility centre upon realizing that the approach was not helping in achieving their desired outcome. Conclusion Infertility is a source of suffering for most women diagnosed with it, resulting in significant negative experiences in their matrimonial homes, families, friends, and the community at large. Most participants rely on spiritual and social support as their immediate and basic coping strategies. Future research could evaluate the treatment and coping strategies and also determine the outcomes of other forms of treatment for infertility.